Analisis Pengukuran Kinerja dengan Menggunakan Metode Balanced Scorecard Pada PT X - Niki, Ni Nyoman; Ayu Sista Dewi, Desak (Dinasti Research, 2024)
PT X is a company engaged in corporate vehicle rental that still uses the traditional method of measuring the company's performance, namely by measuring the financial aspect only, even though the performance measurement only by looking at the financial aspects still has a weakness, so it is needed to measure the company's performance effectively, one of which is using the balanced scorecard method. There are four balanced scorecard perspectives, namely: (1) financial perspective, (2) customer perspective, (3) internal business process perspective, (4) learning and growth perspective. The purpose of this research to determine the performance of PT X is reviewed from four perspectives. Data collection in this research is carried out by interview and observation, then the data collected is analyzed by the balanced scorecard method. The results of this study showed that the performance of PT X which was measured with four perspectives in the balanced scorecard considered to be quite good while still needing to be improved